BOOSTING STUDENT NATIONALISM CHARACTER THROUGH NATIONAL HISTORY - Retno Wigati (STKIP NU Kabupaten Tegal, 2023)
Teaching national character to students requires an exemplary context from parents, teachers, and community leaders. This research is a literature review obtained based on documents stipulated by the Ministry of Education and Culture of the Republic of Indonesia on the policy of strengthening students to the Pancasila student character as a national character. This is a perception of the diversity that is owned by the Indonesian nation which certainly requires a touch of multiculturalism as a whole. The conclusion drawn from this paper is that the government and all stakeholders need to work together to ensure the strengthening of the example of teachers, parents and all parties so that students directly follow what should be done in solving every problem with a simple solution but the problem is resolved.